Comparative Analysis of Emotional Symptoms in Elderly Koreans with Hwa-Byung and Depression - Im, Chae-Sung; Baeg, Sengmi; Choi, Jin-Hoon; Lee, Miji; Kim, Hyun-Jin; Chee, Ik-Seung; Ahn, So-Hyun; Kim, Jeong Lan (Psychiatry investigation, 2017)
This study compared the symptomatic emotional traits of elderly South Korean patients with hwa-byung and those with depression. We enrolled 58 patients with hwa-byung, 180 patients with depression, and 181 healthy control subjects. All participants completed the Hwa-byung Scale, Hamilton Depression Rating Scale (HDRS), Beck Depression Inventory (BDI), Geriatric Depression Scale (GDS), State Trait Anger Expression Inventory (STAXI), Reaction Inventory (RI), and Aggression Questionnaire (AQ). Chi-square tests and a one-way analysis of variance with Games-Howell post-hoc tests were used to compare demographic variables and scores. A binary logistic regression analysis was used to examine risk factors for hwa-byung. Scores in the hwa-byung group were higher than those in the depression group for the HDRS; BDI; GDS; trait anger STAXI subscale (trait anger temperament and trait anger reaction); state anger and anger expression STAXI subscales (anger-in, anger-out, and anger control); physical and verbal aggression as well as anger and hostility AQ subscales; and disturbance, embarrassing circumstances, personal disrespect, and unpleasant encounters RI subscales. A binary logistic regression analysis demonstrated that the state anger STAXI subscale, verbal aggression and anger AQ subscales, and unpleasant encounters RI subscale were significantly associated with hwa-byung. Elderly patients with hwa-byung had more severe anger traits and states as well as higher depression severity compared to those diagnosed with clinical depression. Excessive anger and anger reactivity to unpleasant factors may be risk factors for hwa-byung, whereas the appropriate expression (rather than suppression) of anger may decrease the risk of hwa-byung.